Download presentation
Presentation is loading. Please wait.
Published byLinette Young Modified over 9 years ago
1
Complex Numbers XII – STANDARD MATHEMATICS
2
If n is a positive integer, prove that
4
If a = cos 2 + isin 2 , b = cos2 + isin 2 , c = cos 2 + isin 2 . Prove that (i) a = cos 2 + isin 2 b = cos 2 + isin 2 c = cos 2 + isin 2 abc = (cos 2 + isin 2 )(cos 2 + isin 2 ) (cos 2 + isin 2 ) = cos (2 + 2 + 2 ) + isin (2 + 2 + 2 )
5
= cos ( + + ) + isin ( + + ) ……..(1) = cos ( + + ) – i sin ( + + ) …….(2) adding (1) and (2) we get
6
= (cos 2 + isin 2 )(cos 2 + isin 2 )(cos 2 + isin 2 ) – 1 = (cos 2 + isin 2 )(cos 2 + isin 2 )(cos 2 – isin 2 ) = (cos 2 + isin 2 )(cos 2 + isin 2 )(cos (–2 ) + isin (–2 )) = cos(2 + 2 – 2 ) + isin(2 + 2 – 2 ) = cos 2( + – ) + isin 2( + – )………….(1) If a = cos 2 + isin 2 , b = cos2 + isin 2 , c = cos 2 + isin 2 . Prove that (ii)
7
= [cos 2( + – ) + i sin 2( + – )] -1 = cos 2( + – ) – i sin 2( + – )………(2) Adding (1) and (2), we get,
8
Simplify: (cos + isin ) 0 = 1
9
Simplify:
10
Prove that:
12
If cos + cos + cos = 0 = sin + sin + sin : prove that (i) cos 3 + cos 3 + cos 3 = 3cos( + + ) (ii) sin 3 + sin 3 + sin 3 = 3sin( + + ) Given: cos + cos + cos = 0 and sin + sin + sin = 0 (cos + cos + cos ) + i(sin + sin + sin ) = 0 (cos + isin )(cos + isin )(cos + isin ) = 0 Let a = cos + isin b = cos + isin c = cos + isin
13
If a + b + c = 0, then a 3 + b 3 + c 3 = 3abc (cos + isin ) 3 + (cos + isin ) 3 + (cos + isin ) 3 = 3(cos + isin )(cos + isin )(cos + isin ) (cos 3 + isin 3 ) + (cos 3 + isin 3 ) + (cos 3 + isin 3 ) = 3[cos ( + + ) + isin ( + + )] (cos 3 + cos 3 + cos 3 ) + i(sin 3 + sin 3 + sin 3 ) = 3cos ( + + ) + 3isin ( + + ) Equating real and imaginary parts cos 3 + cos 3 + cos 3 = 3cos ( + + ) sin 3 + sin 3 + sin 3 = 3sin ( + + )
14
If n is a positive integer, prove that (i) (1 + i) n + (1 – i) n = Let 1 + i = r(cos + isin )
15
Substituting i = - i Adding (1) and (2), we get
17
If n is a positive integer, prove that (ii) ( 3 + i) n + ( 3 – i) n = Let 3 + i = r(cos + isin )
18
Substituting i = –i Adding (1) and (2), we get
20
If n is a positive integer, prove that (1 + cos + isin ) n + (1 + cos - isin ) n (1 + cos + isin ) n + (1 + cos - isin ) n
22
If and are the roots of x 2 – 2x + 4 = 0 prove that n – n = i2 n+1 sin (n /3) and deduce 9 – 9 x 2 – 2x + 4 = 0 a = 1, b = –2, c = 4 The two roots are
23
Let 1 + i 3 = r(cos + isin )
24
Substituting i = –i we get Subtracting (2) from (1) we get
25
If n = 9 9 – 9
26
If x + 1/x = 2cos prove that (i)x n + 1/x n = 2cos n (ii) x n – 1/x n = 2isin n
28
If x + 1/x = 2cos , y + 1/y = 2cos , prove that one of the values of
29
similarly
30
Adding (1) and (2)
31
Solve: x 8 + x 5 – x 3 – 1 = 0 x 8 + x 5 – x 3 – 1 = 0 x 5 (x 3 + 1) – (x 3 + 1) = 0 (x 3 + 1)(x 5 – 1) = 0 x 3 + 1 = 0, x 5 – 1 = 0 Case (1) x 3 + 1 = 0 x 3 = – 1 = cos + isin = cos(2k + ) + isin(2k + ) x = {cos(2k + ) + isin(2k + )} 1/3
32
The three values are Case (2) x 5 – 1 = 0 x 5 = 1 = cos 0 + isin 0 = cos(2k ) + isin(2k ) x = {cos(2k ) + isin(2k )} 1/5
33
The five values are
34
Solve: x 7 + x 4 + x 3 + 1 = 0 x 7 + x 4 + x 3 + 1 = 0 x 4 (x 3 + 1) + (x 3 + 1) = 0 (x 3 + 1)(x 4 + 1) = 0 x 3 + 1 = 0, x 4 + 1 = 0 Case (1) x 3 + 1 = 0 x 3 = – 1 = cos + isin = cos(2k + ) + isin(2k + ) x = {cos(2k + ) + isin(2k + )} 1/3
35
The three values are Case (2) x 4 + 1 = 0 x 4 = – 1 = cos + isin = cos(2k + ) + isin(2k + ) x = {cos(2k + ) + isin(2k + )} 1/4
36
The four values are
37
Find all the values of (1 + i) 1/4 Let 1 + i = r(cos + isin )
38
For k = 0,1,2,3,4 we get all the values
39
Find all the values of And hence prove that the product of the values is 1 Since sin is – ve and cos is +ve lies in the fourth quadrant
40
For k = 0,1,2,3, we get all the values
41
Their product = = 1
42
x 2 – 2px + (p 2 + q 2 ) = 0 a = 1, b = –2p, c = p 2 + q 2 The two roots are If and are the roots of x 2 – 2px + (p 2 + q 2 ) = 0 and tan = q/ y+p prove that
45
P represents the variable complex number z, find the locus of P if Let z = x + iy be the variable complex number
46
x(x + 1) + y(y + 1) = x 2 + (y + 1) 2 x 2 + x + y 2 + y = x 2 + y 2 + 2y + 1 x + y = 2y + 1 x – 2y + y – 1 = 0 x – y – 1 = 0 The locus of P is x – y – 1 = 0
47
Find the square root of – 8 – 6i. Let square root of – 8 – 6i be x + iy – 8 – 6i = (x + iy) 2 = x 2 + 2ixy + i 2 y 2 = x 2 + 2ixy – y 2 – 8 – 6i = x 2 – y 2 + 2ixy Equating the real and imaginary parts x 2 – y 2 = – 8 ……..(1) 2xy = –6 ……..(2) xy = –3 y = –3/x Sub y = –3/x in (1)
48
x 4 – 9 = – 8x x 4 + 8x 2 – 9 = 0 x 4 + 9x 2 – x 2 – 9 = 0 x 2 (x 2 + 9) – 1(x 2 + 9) = 0 (x 2 + 9)(x 2 – 1) = 0 x 2 = –9, 1 x = ±3i, ±1 Since is real x = ±1 If x = 1, then y = –3 If x = –1, then y = 3 The square root = 1 – 3i and –1 + 3i
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.